The Qowaid Learning Revolution: Blending Microlearning with Digital Economy Opportunities - Hibatin Wafiroh; Moh. Sholeh Afyuddin; Intan Nur'aini; Ela Febrian; Alifatul Nur Dita Maharani (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The development of digital technology has brought significant transformation in the field of education, including Arabic language learning. One of the platforms widely utilized for learning is YouTube, which offers flexibility and ease of access. Qowaid, as a branch of Arabic linguistics encompassing nahwu (syntax) and sharaf (morphology), is often considered complex and requires an effective learning approach. Microlearning, with its characteristics of being concise, focused, and structured, offers a solution to facilitate the understanding of qowaid material. The YouTube channel Yayasan BISA was selected as the subject of this study due to its popularity and systematic presentation of materials. This research aims to analyze the qowaid learning content on the Yayasan BISA YouTube channel through the lens of microlearning. The method used is qualitative with a content analysis approach. Data were collected through documentation of qowaid learning videos on the channel, which were then analyzed based on three microlearning elements: microcontent, pedagogy, and technology. The findings reveal that out of 23 qowaid learning playlists on the Yayasan BISA channel, only two playlists—Nahwu Animation and Sharaf Animation—meet the principles of microlearning. These videos are typically short in duration (4–6 minutes), focused on a single topic, and presented with engaging animations. However, aspects such as retention reinforcement, interactivity, and learning evaluation still need to be improved to support more comprehensive learning effectiveness